2008
DOI: 10.1088/0953-8984/20/23/235230
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and elastic constants of zirconium from first-principles calculations

Abstract: Using the projector augmented wave (PAW) within the Perdew-Burke-Ernzerhof (PBE) form of the generalized gradient approximation (GGA), we investigate the effect of hydrostatic pressure on the structures of zirconium metal at zero temperature. We obtain the [Formula: see text] transition at around 26.8 GPa, which is in excellent agreement with the experimental values. We also find that the ω phase is most stable at 0 K and 0 GPa. This conclusion is supported by first-principles calculations of Schell et al and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 51 publications
5
13
0
Order By: Relevance
“…Published theoretical/experimental data on the elastic constants for the chosen alloys are not available for comparison. Comparison for the present values to theoretical/experimental studies of pure metals, as shown in Table 1, demonstrates that results obtained from the present investigation are higher than those of the pure metals as reported by other investigators [24,25]. The obtained values of the SOEC and TOEC are of the same order as previous experimental and theoretical studies of other metallic alloys and metals [19,21,[26][27][28].…”
Section: Resultssupporting
confidence: 81%
“…Published theoretical/experimental data on the elastic constants for the chosen alloys are not available for comparison. Comparison for the present values to theoretical/experimental studies of pure metals, as shown in Table 1, demonstrates that results obtained from the present investigation are higher than those of the pure metals as reported by other investigators [24,25]. The obtained values of the SOEC and TOEC are of the same order as previous experimental and theoretical studies of other metallic alloys and metals [19,21,[26][27][28].…”
Section: Resultssupporting
confidence: 81%
“…By comparing the enthalpies of a-, x-and b-Zr, we found that the stable phase is a-Zr at zero pressure and temperature. The a-Zr transforms to x-Zr and then to b-Zr occurs at 0.98 GPa and 31.6 GPa at zero temperature, which agree with the theoretical results [35][36][37][38]. The transition pressures at high temperature will be discussed subsequently in the P-T phase diagram section.…”
Section: Static Structural Propertiessupporting
confidence: 85%
“…They are widely used in aerospace industry due to their light weight, static strength, stiffness and oxidation resistance. [1,2,3,4,5,6,7] This especially concerns their aluminides, Zr 3 Al and Ti 3 Al, which are important in high temperature applications. [8,9,10,11,12] Titanium rich and zirconium ternary aluminides can be obtained by mixing Zr 3 Al and Ti 3 Al.…”
Section: Introductionmentioning
confidence: 99%